Electronic E-sport’sThailand : Opinion & Movement from social and Public Policy - Udomsook, Kanchanat (Research and Development Journal Sisaket Rajabhat University, 2019)
Currently, it is estimated that there are about 27.5 million audience E-Sports in Thailand, evaluating from Video and online gamers, is the news sport accepted and recognized even by Thai governments and provides an opportunity for substantial income E-sports. There are necessary for Thai people to understand and concern about E-sports that are basically video games, and the main concern is the number of young people who are addicted to online and video games. So we collect the several opinions of Electronic E-sport Game in Thailand from stakeholder ; policy maker, Thailand’s game sector, business and marketing E-Sports teams, lecturers and general people for informing in 3issues ; 1) Is an E-sport a real sport? 2) Good or bad that E-sport as a sport 3) Is Thailand ready for the global E-sports hype?Finally the aims of the article is; to inform and to inspire to research about E-Sports in Thailand in next issue